En naturfilosof efter Grundtvigs hjerte - Larsen, Ejvind (Grundtvig-studier, 1973)
A Natural philosopher after Grundtvigs heart By Ejvind Larsen This essay is a chapter from the book on Grundtvig and Marx which Ejvind Larsen wrote after the paper that he read at the International Grundtvig Seminar in August 1972. The fundamental idea in this essay is that Shakespeare was of greater importance to Grundtvig - and incidentally also to Marx – than has hitherto been recognized. In the introduction to Nordic Mythology (1832), Grundtvig refers in a footnote to the, as he calls it, “ classic passage (As You Like It, Act III, Scene III) beginning: Hast thou any philosophy in thee, shepherd?”. If one looks this up, it becomes apparent that the shepherd’s simple answer to Touchstone’s question, being based as it is on experience and common sense, corresponds absolutely to Grundtvig’s views on the philosophy of nature of his own time - and especially of Schelling.Ejvind Larsen thus rejects Kaj Thaning’s interpretation of Grundtvig’s statement from the same book, that he will be able to collaborate with “naturalists with spirit”. What Grundtvig is here rejecting is, according to Thaning, something “ animal, merely biological” . This interpretation is at variance partly with a draft from 1834 (in which what Grundtvig rejects is on the contrary, “ fervent sollicitude for one’s neighbour’s immortal soul”), partly with Grundtvig’s works up to 1832, the year which, according to Thaning, marks a decisive break with the past in virtually every sphere in Grundtvig’s world. Ejvind Larsen asserts furthermore that the correct interpretation of the following sentence is to be found in the very work that marks the turning-point: “ The naturalist must be far more concerned about a spiritual science that explains human life, than we are, for to us it is only, properly understood, an earthly matter, but to him it is a question of salvation” . (Selected Works, 1948, IV p. 59).Through quotations from Grundtvig’s works from 1810 to his death and Henning Høirup’s thesis, “ Grundtvig’s View of Faith and Cognition” (1949), Ejvind Larsen establishes1) that throughout those years Grundtvig asserted that “ the secret of salvation is concealed from the learned and the wise” , namely, in Grundtvig’s own age the idealistic philosophy and theology which established a hierarchy separating the wise from the innocent, and2) that consequently, in Kirkens Gienmæle (1825) he claimed that the testimony he was seeking as to what true Christianity is, was quite simply to be found in the Apostles’ Creed at baptism, and finally3) that the mistake lay in Kant’s moral philosophy having been accepted at its face value (Høirup, p. 181 ff).“ The fundamental error of Kantianism is, according to Grundtvig, the assertion about human independence and the invalidity of experience” (draft from 1824). It annoyed Grundtvig that this moral philosophy should, “with blind faith” , be accepted by everyone, thereby binding the faith of the uneducated to the testimony of the learned.Shakespeare’s shepherd, Corin, however, does not kneel to himself and does not worship his own reason as God. Despite the fact that he is not a Christian. Grundtvig, then, realized in 1832 that there is no need of any Christian faith to defend the people against the papacy of the learned philosophers and theologians.All that is needed is the experience and common sense that a simple shepherd possesses. It is the natural philosophy of the people that Grundtvig extols, the most essential proposition of which is “ that a great cause of the night is lack of the sun” .In 1814 Grundtvig protested against Schelling because he explicitly said, “ that darkness is that from which light originated“ . And in August 1872, for the same reason, he asked Ernst Trier to alter a line in one of his songs: “ Let light shine out of darkness!” to “ Let light shine through darkness” , remarking, “ for I assure you that light never comes out of darkness.” Darkness is caused by the sun being absent, just as falsehood may be explained as the contrary of truth. Truth explains itself. In the course of history.